PEMBINAAN SEKOLAH BERBUDAYA LINGKUNGAN UNTUK MENDUKUNG PROGRAM ADIWIYATA DI WILAYAH BALI BARAT - Amin Setyo Leksono; Bagyo Yanuwiadi; Zulfaidah Penata Gama; Nia Kurniawan; Muhammad Imam; Elan Herlina (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract Community service activities have been carried out in the West Bali Region. Several schools in the western part of Bali, including Buleleng and Jembrana Regencies, still have not received an Adiwiyata school award. Community service activities were carried out offline with the target group being biology teachers and students from Buleleng and Jembrana Regencies. This activity aims to a) Increase the understanding of teachers and students regarding environmental culture and the independent curriculum to support Adiwiyata schools; b) Increase teacher awareness for the implementation of an independent curriculum to support environmental culture. Participants in the activity consisted of teachers and students. The method of implementing the activities is carried out by surveiing and inventorying problems, interviews, lectures and discussions as well as simulations. Participants in the activity totaled 70 people divided into several topics. Of the 70, 20 of them studied the topic of Adiwiyata schools. The average age of the respondents is 41-50 years, with an undergraduate education level. The level of understanding from the majority knowing little (71%) increased to very knowing (57%). The satisfaction level reached more than 80%, and all participants were willing to follow up on the understanding that had been obtained to develop environmentally cultured schools in the West Bali region. Abstrak Kegiatan pengabdian masyarakat telah dilaksanakan di Wilayah Bali Barat. Bebeapa sekolah di wilayah Bali bagian barat termasuk Kabupaten Buleleng dan Jembrana, masih banyak yang belum mendapat penghargaan sekolah adiwiyata. Kegiatan pengabdian pada masyarakat yang dilaksanakan secara luring dengan target kelompok sasarannya adalah guru bidang biologi dan siswa dari Kabupaten Buleleng dan Jembrana. Kegiatan ini bertujuan untuk a) Meningkatkan pemahaman guru dan siswa mengenai mengenai budaya lingkungan dan kurikulum merdeka untuk mendukung sekolah adiwiyata; b) Meningkatkan kesadaran guru untuk penerapan kurikulum merdeka untuk mendukung budaya lingkungan. Peserta kegiatan terdiri dari guru dan siswa. Adapun metode pelaksanaan kegiatan dilakukan dengan survei dan inventarisasi masalah, wawancara, ceramah dan diskusi serta simulasi. Peserta kegiatan berjumlah 70 orang yang terbagi dalam beberapa topik. Dari 70, 20 diantaranya mendalami topik tentang sekolah adiwiyata. Usia responden rata-rata 41-50 tahun, dengan tingkat pendidikan sarjana. Tingkat pemahaman dari mayoritas sedikit tahu (71%) meningkat menjadi sangat mengetahui (57%). Tingkat kepuasan mencapai lebih dari 80%, dan seluruh perserta bersedia untuk menindaklanjuti pemahaman yang telah diperoleh untuk mengembangkan sekolah berbudaya lingkungan di wilayah Bali Barat.